2022
DOI: 10.3174/ajnr.a7617
|View full text |Cite
|
Sign up to set email alerts
|

Endarterectomy, Stenting, or Medical Treatment for Symptomatic Carotid Near-Occlusion: Results from CAOS, a Multicenter Registry Study

Abstract: BACKGROUND AND PURPOSE:The treatment of symptomatic carotid near-occlusion is controversial. Our aim was to analyze the results of carotid endarterectomy and carotid artery stent placement in patients with symptomatic carotid near-occlusion and to identify factors related to technical failure, periprocedural complications, and restenosis. MATERIALS AND METHODS:We conducted a multicenter, prospective nonrandomized study. Patients with angiography-confirmed carotid near-occlusion were included. We assessed the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 28 publications
(43 reference statements)
0
4
0
Order By: Relevance
“…In their current study, which included 141 CNO patients, Garcia-Pastor et al 6 reported that they performed CEA on 23 patients. And they reported the CEA procedure success rate at 83.6% and also reported the rate of periprocedural ischemic stroke or death at 13%.…”
Section: Discussionmentioning
confidence: 78%
See 3 more Smart Citations
“…In their current study, which included 141 CNO patients, Garcia-Pastor et al 6 reported that they performed CEA on 23 patients. And they reported the CEA procedure success rate at 83.6% and also reported the rate of periprocedural ischemic stroke or death at 13%.…”
Section: Discussionmentioning
confidence: 78%
“…Consistent with these findings, they reported that revascularization is associated with high technical failure and perioperative complications in patients with CNO. 6 On the contrary, in their meta-analysis, Meershoek et al 13 evaluated 17 CNO patients undergoing CEA, and the 30-day stroke or death rate was reported to be 1.8% in these patients. When the results were compared with the results of non-CNO patients 14 undergoing CEA in the literature, it was reported that the CNO patients were not at high risk for surgery.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…[63] Both CAS and CEA are associated with high rates of failure and periprocedural stroke.51 When the carotid artery is nearly completely occluded, revascularization has not been shown to reduce the risk of stroke as compared to just medical treatment. [30] It has also been shown that long-term complications are less for CAS than for CEA. [46] CEAs also come with operative complications to consider.…”
Section: Complications Of Carotid Endarterectomy and Carotid Artery S...mentioning
confidence: 99%